The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s10157-006-0416-9
|View full text |Cite
|
Sign up to set email alerts
|

True hyponatremia secondary to intravenous immunoglobulin

Abstract: Hyponatremia is characterized as either "true hyponatremia," which represents a decrease in the Na(+) concentration in the water phase of plasma, or "pseudohyponatremia," which is due to an increased percentage of protein or lipid in plasma, with a normal plasma water Na(+) concentration ([Na(+)]). Pseudohyponatremia is a known complication of intravenous immunoglobulin (IVIG). Because IVIG has been reported to result in post-infusional hyperproteinemia, IVIG-induced hyponatremia has been attributed to pseudoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…9 Given this fact, it has been suggested that the term "pseudohyponatremia" no longer be used. 1 This argument is supported by recent reports on the presence of true hyponatremia in patients with multiple myeloma 10 and in those who had received in- travenous immunoglobulin infusions, 11 conditions that previously were associated with pseudohyponatremia. The exact incidence of hyponatremia in patients with INS and severe edema is not known.…”
Section: Discussionmentioning
confidence: 63%
“…9 Given this fact, it has been suggested that the term "pseudohyponatremia" no longer be used. 1 This argument is supported by recent reports on the presence of true hyponatremia in patients with multiple myeloma 10 and in those who had received in- travenous immunoglobulin infusions, 11 conditions that previously were associated with pseudohyponatremia. The exact incidence of hyponatremia in patients with INS and severe edema is not known.…”
Section: Discussionmentioning
confidence: 63%
“…Correlation of gravimetrically determined PWC with protein/lipiddetermined PWC by linear regression. compartment to the extracellular compartment as well as the infusion of large volume of dilute fluids in patients with an underlying defect in urinary free water excretion (7). In this setting, extrapolation of the true [Na ϩ ] D-ISE from the [Na ϩ ] I-ISE can be especially helpful in the serial analysis of [Na ϩ ] p during treatment of the true hyponatremia.…”
Section: Discussionmentioning
confidence: 99%
“…Sucrose causes to hyponatremia by providing fluid passage from the intravascular area into the extravascular area and free water causes to hyponatremia by creating water load mostly in individuals with tubular damage (15).…”
Section: B) Thromboembolic Complicationsmentioning
confidence: 99%